Redescription of Entomobrya schoetti (Collembola, Entomobryidae, Entomobryinae), third record to the world fauna - Jordana, R.=700 1 Baquero, E.
Resumenes (Es, En)
14 fig a color; 3 ref.
Keywords: COLLEMBOLA; IDENTIFICACION; MICROSCOPIA; ALFALFA; SMINTHURUS VIRIDIS; REDESCRIPCION